The Determinants of Long‐Term Corporate Debt Issuances - BADOER, DOMINIQUE C.; JAMES, CHRISTOPHER M. (Journal of Finance, 2016)
ABSTRACT A significant proportion of the debt issued by investment‐grade firms has maturities greater than 20 years. In this paper we provide evidence that gap‐filling behavior is an important determinant of these very long‐term issues. Using data on individual corporate debt issues between 1987 and 2009, we find that gap‐filling behavior is more prominent in the very long end of the maturity spectrum where the required risk capital makes arbitrage costly. In addition, changes in the supply of long‐term government bonds affect not just the choice of maturity but also the overall level of corporate borrowing.